2021
DOI: 10.1177/1744987120979344
|View full text |Cite
|
Sign up to set email alerts
|

The effect of patient safety culture on nurses’ near-miss reporting intention: the moderating role of perceived severity of near misses

Abstract: Background Reporting near misses is a practical approach to improve the confounding challenge of patient safety. Evidence suggests that patient safety culture and the characteristics of errors might have important impacts on reporting. No studies, however, have examined the relationships among patient safety culture, perceived severity of near misses and near-miss reporting. Aims To explore the relationship between patient safety culture and nurses’ near-miss reporting intention, and examine the potential mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…In addition, the score of barriers to reporting adverse events was significantly and positively correlated with reporting intention; that is, the more the nurses perceived barriers to reporting, the less their reporting intention. Of these, reporting culture had the greatest impact on nurses’ intention to report adverse events, consistent with the findings of Yang et al 56 and Toren et al 57 Previous studies have pointed out that fear of discrimination and punishment is the main reason why nurses do not volunteer to report adverse events. 58 , 59 Similar to Lee et al, 60 we also found that the perceptions of reporting benefits influences nurses’ reporting intentions.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, the score of barriers to reporting adverse events was significantly and positively correlated with reporting intention; that is, the more the nurses perceived barriers to reporting, the less their reporting intention. Of these, reporting culture had the greatest impact on nurses’ intention to report adverse events, consistent with the findings of Yang et al 56 and Toren et al 57 Previous studies have pointed out that fear of discrimination and punishment is the main reason why nurses do not volunteer to report adverse events. 58 , 59 Similar to Lee et al, 60 we also found that the perceptions of reporting benefits influences nurses’ reporting intentions.…”
Section: Discussionsupporting
confidence: 86%
“…To promote communication openness, a comprehensive provider or team communication strategy that includes a structured communication tool, a standardized escalation mechanism, daily multidisciplinary patient-centered rounds with a daily objectives sheet, and team huddles can be implemented. The SafetyNET (an organization-wide patient safety network comprised of education, an online interactive discussion forum, and a recognition program or newsletter), which has been shown to improve overall safety event reporting and minimize moderate-adverse classified events, may also be implemented [ 29 ]. However, these ideas must be evaluated for their usefulness in the current context.…”
Section: Discussionmentioning
confidence: 99%
“…Despite efforts over the past few decades, patient safety remains an important topic of interest because of the rate of safety errors in the medical environment [1]. During this period, the importance for medical institutions to develop a culture centered on support and learning, in order to improve patient safety, was established [2]. The present focus should be on a more fundamental part of building patient safety culture, related to the psychological aspects of its members.…”
Section: Introductionmentioning
confidence: 99%